2017
DOI: 10.1002/aic.15894
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis and optimization of power generation in pressure retarded osmosis: Effect of multistage design

Abstract: This work presents a systematic method for analysis and optimization of specific energy production (SEP) of pressure retarded osmosis (PRO) systems employing single-stage configuration as well as multistage design with interstage hydro-turbines. It is shown that the SEP normalized by the draw solution feed osmotic pressure increases with the number of stages as well as a dimensionless parameter c tot 5A tot L p p 0 =Q 0 . As compared to the single-stage PRO, the multistage arrangement not only increases flux a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Research into multistaging of PRO for improved performance is still in its infancy, with no clear multistage configurations identified for maximizing PRO performance. This is because researchers [13][14][15][16] have used different performance metrics and analyzed contrasting multistage configurations without sufficient theoretical justification or a common design philosophy. This makes it difficult to compare different multistage designs available in the literature in a coherent manner.…”
Section: Pro Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Research into multistaging of PRO for improved performance is still in its infancy, with no clear multistage configurations identified for maximizing PRO performance. This is because researchers [13][14][15][16] have used different performance metrics and analyzed contrasting multistage configurations without sufficient theoretical justification or a common design philosophy. This makes it difficult to compare different multistage designs available in the literature in a coherent manner.…”
Section: Pro Modulementioning
confidence: 99%
“…Hence, it is difficult to compare the disparate multistage configurations against one another. Different systems even have opposing design philosophies: interstage pressurization in [20] as opposed to interstage depressurization in [13,16], as well as parallel [14,16] vs. countercurrent [13,20] flow of feed and draw streams.…”
Section: Qpmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is shown that multistage design with interstage turbines improves both power generation and power density (PD) on the basis of the same membrane area. 4 Recently, batch or semibatch operation of RO has caught attention because it can potentially reduce SEC by recycling the retentate stream and applying a time-dependent pressure. The early concept was originated by Efraty in late 2000s when he named it "closed-circuit desalination".…”
Section: Introductionmentioning
confidence: 99%
“…Salinity gradient processes experiences dynamic changes in the full-scale PRO element due to the continuous dilution and concentration of the draw and feed solutions, respectively [3,9,23]. M. Li [12,13] provided a dimensionless design model to evaluate the impact of operating parameters on the performance of the PRO process. The study concluded that the concentration and dilution of feed and draw solutions, respectively, reduces the power density and the optimal ∆𝑃𝑃 shifts away from ∆𝜋𝜋/2 value.…”
Section: Introductionmentioning
confidence: 99%